2014
DOI: 10.1111/bpa.12235
|View full text |Cite
|
Sign up to set email alerts
|

A 24 Year‐Old Woman with Relapsing Brainstem Manifestations and Multiple Focal Brain Lesions

Abstract: A 24 year-old white right handed woman with an otherwise unremarkable medical and family history was admitted with vertigo, hiccups, intractable vomiting, gait unsteadiness and oscillopsia that developed gradually over 9 months.Although initially relapsing and remitting, her manifestations became persistent approximately one month prior to her admission. Neurological examination revealed periodic alternating nystagmus, gait ataxia and bilaterally brisk tendon reflexes in upper and lower extremities and a right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…PBSL mainly affected adults in their sixth decade with a slight male predominance. Parallel to previous case reports [6][7][8][9][10][11][12][13][14][15][16][17][18], our study con rmed that all PBSLs were NHLs. The prognosis of PBSL is poor.…”
Section: Clinical Features Survival and Prognostic Factors Of Pbslsupporting
confidence: 88%
See 1 more Smart Citation
“…PBSL mainly affected adults in their sixth decade with a slight male predominance. Parallel to previous case reports [6][7][8][9][10][11][12][13][14][15][16][17][18], our study con rmed that all PBSLs were NHLs. The prognosis of PBSL is poor.…”
Section: Clinical Features Survival and Prognostic Factors Of Pbslsupporting
confidence: 88%
“…But PCNSL located at the brainstem predicts more severe surgical complications [5]. At present, there are only several case reports from a single institute [6][7][8][9][10][11][12][13][14][15][16][17][18]. The existing published studies failed to estimate the survival of PBSL, let alone to explore survival-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…A biopsy showed infiltration of intermediate-sized agranular lymphocytes expressing TdT and CD56 with absence of all myeloid, B-cell, and T-cell markers. An assessment of TCR and IgH gene rearrangement resulted negative, and based on these findings the diagnosis of precursor NK cell lymphoblastic leukaemia/lymphoma was made [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cytogenetic evaluation showed no specific recurrent genetic abnormalities for ALL; however, there was a tumour clone with translocation between the short arm of chromosome 1 at p36.1 and the long arm of chromosome 14 at q24 and isochromosome 17q as a clonal evolution. FISH analysis confirmed that the TP53 gene was deleted in 14% of the studied cells and was negative for ALL panel-specific abnormalities; the cytogenetic result was as follows: 46,XY,t(1; 14)(p36.1;q24)[ 3 ]/46,XY,idem,i(17)(q10)[ 2 ]/46,XY[ 5 ]. nuc ish(ABL1,BCR)x2[100]/(ETV6,RUNX1)x2[100]/(5′MLL,3′MLL,5′MLL con 3′MLL)x2[100]/(5′MYC,3′MYC,5′MYC con 3′MYC)x2[100]/(TCF3,PBX1)x2[100]/(TP53€1)[28/200].…”
Section: Case Historymentioning
confidence: 91%
See 1 more Smart Citation